Entre maracás, curimbas e tambores: pajelanças nas religiões afro-brasileiras - QUINTAS, Gianno Gonçalves (Universidade Federal do Pará, 2014)
The purpose of this dissertation is to study the pajelança in the city of Belém, place where most of the accomplished studies if it concentrates in the decade of 1970 and 1980, or it has as investigation locus the countryside of the state of Pará. Some articles of Vicente Salles (1969) and Napoleão Figueiredo (1994) point to disappearance of the "pure" pajelança in Belém. This disappearance was due, in great measure, to the “influence” of the umbanda. Thus, the objective is to understand, starting from the study of four terreiros, as that practice is constituted in the city of Belém under the context of the Afro-Brazilian religions. The pajelança or “pena e maracá”, as it is known, is characterized, basically, in the faith of "encantados", that "incorporate", during the rituals, in the pajé, who is the central character of the sessions.